IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PEMELIHARAAN MESIN KENDARAAN RINGAN SISWA KELAS XI OD SMK YAPPI WONOSARI - Giri Wahyu Pambudi (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study aims to determine the increase in motivation and learning result of class XI OD at YAPPI Wonosari Vocational High School on light vehicle engine maintenance study through the implementation of a problem based learning model. This research is a classroom action research using the Kemmis and Taggert designs carried out in two cycles. This research was conducted at YAPPI Wonosari Vocational High School with the subject of research is class XI OD. The data collection techniques used are tests and questionnaires. Analysis of the data used is descriptive quantitative data analysis. This research was successful so that the cycle can be stopped if there is an increase in motivation and learning result from cycle one to the next cycle, learning outcomes of 75% of students are able to meet minimum completeness criteri of 75 and 75% of students get motivation values above 75 The results of the study showed that motivation and learning result increased after the use of problem based learning models. This is evidenced by the increase in learning result and learning motivation. The learning results in cycle 1 increased from 77 to 82.96 with a percentage of completeness of 62.96% and in cycle 2 it increased from 82.96 to 88.19 with the percentage of completeness 88.88%. Students learning motivation in cycle 1 increased from 74.72 to 77.04 with the percentage of students who got motivation scores above 75 by 55.56% and in cycle 2 it increased from 77.04 to 79.63 with the percentage of students who got motivation scores above 75 by 77.77%